2013
DOI: 10.1002/prs.11623
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis by means of a QRA approach on a LPG cylinder filling installation

Abstract: In recent years in the process industries much attention has been paid to the quantitative risk analysis (QRA). This study describes a QRA evaluating the risk from the operation of an LPG installation. Both individual and societal risks to the installation personnel, customers, and neighbors/passerbys are evaluated. The study showed that the largest effect is caused by a jet fire and flash fires. Unacceptable individual risk is being imposed on personnel, consumers, and third parties. Societal risks are also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…The study by Kariznovi et al, (2017) (7) as well as a research by Dormohammadi et al, (2014) (6) showed that the weather condition has an impact on the severity of eruptive and abrupt fire (6,7), which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study by Kariznovi et al, (2017) (7) as well as a research by Dormohammadi et al, (2014) (6) showed that the weather condition has an impact on the severity of eruptive and abrupt fire (6,7), which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the release of chemical substances from the process plants is a significant hazard in process industries, which may endanger the staff and public health within the vicinity of such facilities. A brief review of the history of refinery incidents reveals that gas -related disasters have frequently occurred over the previous decades (6)(7)(8). Given the above -mentioned examples, it must be noted that consequence evaluation of hazards such as fire and discharge of substances from the oil and gas reservoirs is a crucial step in order to enhance the level of safety in existing or developing units (9).…”
Section: Introductionmentioning
confidence: 99%
“…PHAST is a professional simulator used for CM in chemical process risk assessments . More description of CM that is used in this work may be find in previous work of the authors . At the end, risk has been estimated by multiply of occurrence probability and severity (lethality numbers in this work) of a given scenario.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…This simulator is specially validated for the release of hydrogen [27] and it is one of the most accurate and precise tool for QRA and consequence modeling [28,29]. It is capable to simulate the progress of a potential incident from its initial leakage to the final possible consequences [23,26]. For the purpose of simulating accident outcomes by PHAST, several assumptions were adopted that include:…”
Section: Consequence Analysismentioning
confidence: 99%
“…In addition, the traditional risk assessment is not adequate to analyze risks in complex systems [22]. The QRA methodology is a proper tool that can be applied to achieve this objective [23].…”
Section: Introductionmentioning
confidence: 99%